Oral Rehabilitation Using Noninvasive Restorative Approach for Late Mixed Dentition of Preterm Birth Child with Amelogenesis Imperfecta - Abdulfatah Alazmah (Case Reports in Dentistry)
Preterm birth children comprise about 6% of live births around the world. It is known that premature children exhibit oral anomalies that could affect the function and/or appearance of their dentition in addition to their medical needs. A diagnosis of amelogenesis imperfecta (AI) can present a challenge for both the patient and the treating clinician. This can be more complicated in the case of child treatment, where cooperation and some of the treatment modalities for adults can not be considered. Conventional management of such children is not possible due to the ongoing process of growth and development and the ability of the child to cope with the extensive and lengthy treatment procedure. This article highlights a minimally invasive method for managing AI using adhesive and full-coverage restoration that requires no tooth preparation; this allows the structural integrity of the teeth to be maintained, along with their vitality. As a result, the child will have teeth with better function and aesthetic, to improve eating, appearance, and self-confidence.